Playful activities in the reinforcement of color learning in children’s post initial education. - Llamuca Maigua, Mónica; Del Pozo Campana, Héctor; Pinos Morales, Geofre (Revista Universidad de Guayaquil, 2018)
In the first school years, the visual materials used in the different activities are important for the acquisition of concepts in the different learning processes such as, for example, the learning of color. This article highlights the results of the before and after application of a guide of playful activities adapted to color learning in high school children. A methodology of qualitative-quantitative type was used where the results of the research are explained, the learning of the color after the application of the guide of playful activities adapted to the color reflects an increase in learning of 20% in relation to the initial analysis. In conclusion, the playful activities reinforce the learning of color in high school children.